Penatalaksanaan Fisioterapi Pada Kondisi Nyeri Punggung Bawah Miogenik Di RSUD Sragen - Anisa Candra, Perwitasari; , Umi Budi Rahayu, SSt. Ft. SPd. M. Kes (2015)
Background: Low back pain miogenik is a sensory and emotional experience which is not pleasant in the area between thorakal 12 to the bottom of the hip or lumbar 5, which arise as a result of damage or potential tissue damage, among others, the damage to the blood vessels, fascia, muscles, tendons, cartilage, ligament, meniscus and exchanges (Paliyama, 2003). Objective: To determine the benefit of Short Wave Diathermy (SWD) and Core Stability Exercises for the reduction of pain, muscle spasm of the vertebrae, increase range of motion, increase muscle strength and functional activity due to increased lower back pain miogenik. Results: After the implementation of the action physiotherapy for six times the results obtained are, decrease the degree of pain, an increase in LGS and increase muscle strength flexor and extensor trunk as follows: painful motion of T1 on a scale of 6 to T6 scale 3, tenderness of T1 scale 4 to T6 scale 1, painful silence of T1 scale 3 to T6 scale 1, LGS on that trunk flexors T1 trunk of 3cm into T6 8 cm, trunk extensor of T1 T6 2cm into 6cm, side flexion of T1 10cm dekstra be T6 12 cm, side The left flexion of T1 12cm fixed 12 cm, increase muscle strength of the trunk flexors T1 is 3 to 4 T6, trunk extensor of T1 T6 3 to 4, side flexion dekstra of T1 T6 3 to 4, and flexion of the left side of the T1 3 to 4. Conclusion: In mitigate problems arising from lower back pain miogenik, physiotherapy with modalities Short Wave Diathermy (SWD) and Core Stability Exercise can reduce pain, reduce muscle spasms in the vetrebra, increase range of motion (LGS) in the trunk, increase muscle strength so that the functional activity of the patient can return to normal.